PELAKSANAAN PERJANJIAN SIMPAN PINJAM KELOMPOK PEREMPUAN PADA UNIT PENGELOLA KEGIATAN PNPM-MP KECAMATAN MENDAHARA - Syarifa Mahila (Jurnal Ilmiah Universitas Batanghari Jambi, 2013)
Rural PNPM Mandiri which is a continuation of activities Development Program (KDP) conducted since 1999 as a government attempt to resolve the poverty that involves elements of society. PNPM Rural create considerable management institutions, both in the village and one of them is sub group Women's Savings and Loans (SPP). Women's Savings and Loans Group Activities (SPP) is an activity of the capital increase for women who have savings and loan activities.Providing assistance in the implementation of women's savings and credit loans among borrowers with the Activity Management Unit (UPK) as advance lender dituangkanlah build an agreement in the form of letter of credit agreement (SPK) containing about your loan term, payment systems, maturity time payment as well as sanctions that they should be according to the provisions of MP PNPM program. Implementation agreement Women's Group Savings and Loans (SPP) PNPM MP in District Mendahara Regency Tanjung Jabung, contained in nine villages. In the implementation of SPP activity is also present in default due to various constraints experienced by group members. The solution put forward to overcome defaults deliberation.Keyword :  agreements, savings and loan , PNPM-MP